Nine stories - Salinger, J. D. (Jerome David), 1919-2010 (Boston : Back Bay Books/Little, Brown, 2001)
Salinger's classic collection of short stories is now available in trade paperback.
Originally published : Little, Brown, 1953.
Keywords: United States -- Social life and customs -- 20th century -- Fiction; Short stories